The pedagogical directive leadership evaluation process and its relationship with the evaluation of the teaching performance of the secondary level in the emblematic educational institution "Mercedes Cabello de Carbonera". Rimac. Ugel 02. Lima 2018 - Flores Espinoza, Leoncio (2021)
The uncertainty and high rate of mistrust that exists between teachers and their governing authorities, especially in pedagogical matters, is one of the key problems in teaching-learning. In this study it was verified that the Pedagogical Directive Leadership is related to the Pedagogical Competences of the Teacher at the secondary level of the “Mercedes Cabello de Carbonera” school. Lima 2018., since it is through a p whose value less than 0.05 in the statistical analysis, such a relationship is demonstrated with an r = 0.768, which is a correlation of 76.8%. And it relates the personal competencies of the teacher whose r = 0.593 is a correlation of 59.3%. Competencies from institutional management have an r = 0.543 which is 54.3%. Communication management competencies have a significant relationship whose r = 0.638, which is 63.8%. It is important to take these correlations into account in order to reduce this gap between weak pedagogical directive leadership and the competencies that the teacher must develop.